Islam and The Early Urban Formation of Mombasa - Dismas Kombo Araka (MIMBAR : Jurnal Sosial dan Pembangunan, 2026)
The study examined the role of religion in the primordial development of Mombasa as an early urban center on the East African coast. While existing historiography largely attributes Mombasa’s emergence to participation in Indian Ocean trade, this study argues that Islam played a central role in shaping the city’s urbanization. Guided by Urbanization Theory and Cultural Diffusion Theory, the study employed a historical research methodology utilizing archival records, oral traditions, historical documents, and scholarly literature. The findings indicate that the spread of Islam from the first millennium CE significantly influenced settlement patterns, governance systems, and social cohesion in Mombasa. Through migration, and scholarly exchanges, Islamic beliefs and institutions were transmitted and adapted within local communities, fostering interaction between indigenous populations and migrants from Arabia and Persia. Rather than replacing indigenous traditions, Islam blended with local practices to create a distinctive Swahili-Islamic culture that enhanced communal identity and political legitimacy. Islamic institutions, including mosques, religious schools, and judicial systems, contributed to the consolidation of urban life. The study concluded that religion was not merely a cultural by-product of trade but a fundamental driver of Mombasa’s early urban formation, helping shape its identity, governance, and long-term development as a prominent Swahili city-state.